2021
DOI: 10.3389/fimmu.2021.645839
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Profiling Identifies Risk Hypoxia-Related Signatures for Ovarian Cancer Prognosis

Abstract: BackgroundOvarian cancer (OC) has the highest mortality rate among gynecologic malignancy. Hypoxia is a driver of the malignant progression in OC, which results in poor prognosis. We herein aimed to develop a validated model that was based on the hypoxia genes to systematically evaluate its prognosis in tumor immune microenvironment (TIM).ResultsWe identified 395 hypoxia-immune genes using weighted gene co-expression network analysis (WGCNA). We then established a nine hypoxia-related genes risk model using le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…Our present work identified that hypoxia-related genes and the risk score model built on them were significantly correlated with the prognosis of CC patients. Similar results were found in ovarian cancer ( Chen et al, 2021 ), triple-negative breast cancer ( Yang et al, 2021a ), osteosarcoma in children ( Jiang et al, 2021a ), acute myeloid leukemia ( Jiang et al, 2021b ), and so on. It indicated that along with other factors, hypoxia might play an important role in the development and progression of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Our present work identified that hypoxia-related genes and the risk score model built on them were significantly correlated with the prognosis of CC patients. Similar results were found in ovarian cancer ( Chen et al, 2021 ), triple-negative breast cancer ( Yang et al, 2021a ), osteosarcoma in children ( Jiang et al, 2021a ), acute myeloid leukemia ( Jiang et al, 2021b ), and so on. It indicated that along with other factors, hypoxia might play an important role in the development and progression of cancer.…”
Section: Discussionsupporting
confidence: 75%
“…The high expression of maspin induced by hypoxia might be associated with a poor prognosis of ovarian clear cell carcinoma ( 57 ). More importantly, although some researchers have identified hypoxia-related genetic signatures to improve the prognosis of patients with ovarian cancer ( 58 , 59 ), they neglected that specific hypoxia-related genes in OC should be analyzed to construct a risk signature. Hence, we performed the identification of specific hypoxia regulators in OC based on cell lines treated with different oxygen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…And it has been proposed that immune checkpoint expression may be a reflection of the clinical outcome of immunotherapy that targets immunological checkpoints ( Zheng et al, 2021 ). Immunotherapy that targets immunological checkpoints (PD-1 and CTLA-4) has recently become a potential treatment option for a variety of malignancies ( Zhou et al, 2017 ; Chen et al, 2021 ). However, each tumor exhibits a different response to immunotherapy ( Zou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%